Reactive oxygen species in cardiovascular disease - Sugamura, Koichi; Keaney, John F. (Free radical biology & medicine, 2011)
Based on the “free radical theory” of disease, researchers have been trying to elucidate the role of oxidative stress from free radicals in cardiovascular disease. Considerable data indicate that reactive oxygen species and oxidative stress are important features of cardiovascular diseases including atherosclerosis, hypertension, and congestive heart failure. However, blanket strategies with antioxidants to ameliorate cardiovascular disease have not generally yielded favorable results. However, our understanding of reactive oxygen species has evolved to the point at which we now realize these species have important roles in physiology as well as pathophysiology. Thus, it is overly simplistic to assume a general antioxidant strategy will yield specific effects on cardiovascular disease. Indeed, there are several sources of reactive oxygen species that are known to be active in the cardiovascular system. This review addresses our understanding of reactive oxygen species sources in cardiovascular disease and both animal and human data defining how reactive oxygen species contribute to physiology and pathology.